A contemporary evaluation of Turkish drug-control policy. (4th March 2018) - Unlu, Ali; Aksu, Gokhan
Abstract: The article provides a contemporary evaluation of Turkish drug-control policy. Turkish drug-control policy is heavily predicated on deterrence-based supply-side policies to the neglect of a holistic strategy that sufficiently addresses supply and demand reduction. The article explores recent subtle trends in drug-control policy to assert that the Turkish government fails to develop appropriate and effective policies in response to the illicit drug issue. In addition, the article identifies and discusses the current political debates and legislative developments that inform the policy preferences of the Turkish authorities. The article concludes that policy failures, combined with the external challenges presented by Syrian refugees and the ongoing insurgency by the Kurdistan Workers' Party (PKK), will result in a substantial prevalence of, and an increase in, drug use and drug-related deaths despite increases in seizure rates, criminal justice cases, and prison population and parolees unless Turkish authorities develop an evidence-based drug-control policy.